Women of Worth: the impact of a cash plus intervention to enhance attendance and reduce sexual health risks for young women in Cape Town, South Africa. Issue 6 (14th June 2022) - Naledi, Tracey; Little, Francesca; Pike, Carey; Edwards, Harley; Robbertze, Dante; Wagner, Colleen; London, Leslie; Bekker, Linda‐Gail
Abstract: Introduction: Conditional cash transfers (CTs) augmented with other interventions are promising interventions for reducing HIV risk in adolescent girls and young women. Methods: A multi‐phase, quasi‐experimental study assessed the impact of a CT (ZAR300; 22) conditional on attending a skills building intervention, Women of Worth (WoW), designed to improve sexual and reproductive health (SRH) outcomes in Cape Town, South Africa from May 2017 to December 2019. The intervention entailed 12 sessions with encouragement to attend adolescent and youth‐friendly health services. Women aged 19–24 years were randomized 1:1 to receive the intervention with a CT ("cash + care" or C+C) or without a CT ("care"). The study included a pilot phase followed by a post‐modification phase with improved uptake and retention without changing programme content or CT. Self‐reported HIV prevalence and SRH/HIV vulnerability were assessed via a self‐administered questionnaire at baseline, after 11 sessions, and 6–30 months' post‐intervention for a subset. Mixed effect logistic regression models were fitted to estimate within‐subject changes in outcomes. Results: Of 5116 participants, 904 (452 participants per arm) were in the pilot and 4212 (2039 "care" participants and 2173 "C+C" participants) were in the post modified phase. There were 1867 (85.9%) and 135 (6, 6%) participants in the "C+C" group and the "Care, " respectively, that were WoW completers (≥ 11 sessions/retention). During the pilot phase, 194 (42.9%) and 18 (4.0%) participants in "C+C" and the "care" groups were retained. Receiving a CT sustained participation nearly 60‐fold (OR 60.37; 95% CI: 17.32; 210.50, p <0.001). Three‐hundred and thirty women were followed for a median of 15.0 months [IQR: 13.3; 17.8] to assess the durability of impact. Self‐reported new employment status increased more than three‐fold ( p <0.001) at WoW completion and was sustained to the longer time point. Intimate partner violence indicators were reduced immediately after WoW, but this was not durable. Conclusions: Participants receiving CT had sustained participation in an SRH/HIV prevention skills building with improvement in employment and some SRH outcomes. Layered, "young woman centred" programmes to address HIV and SRH risk in young women may be enhanced with CT.